Hydrogenated Dilute Nitride Semiconductors: Theory, Properties, and Applications - Ciatto, Gianluca (Jenny Stanford Publishing, 2015)
The nonlinear behavior of nitrogen and the passivation effect of hydrogen in dilute nitrides open the way to the manufacture of a new class of nanostructured devices with in-plane variation of the optical band gap. This book addresses the modifications of the electronic structure and of the optical and structural properties induced in these technologically important semiconductors by atomic hydrogen irradiation. The book comprises discussions on experimental results from several techniques, enriched by state-of-the-art theoretical studies aimed at clarifying the origin of hydrogenation effects that lead to the discovery of specific nitrogen-hydrogen complexes.